A Privacy Violation Behaviors Preventive System in Using Social Media by Graduate Students of King Mongkuts Institute of Technology Ladkrabang - Thatsanee Ngoensuk; Chantana Viriyavejakul (My University, 2019)
Abstract The purpose of this research was to create, test and develop a model for developing a system to protect personal rights violations in using social media, Integrated learning styles using deductive teaching methods and the use of case studies to promote knowledge in developing a model for developing a system to protect personal rights violations in the use of social media of graduate students at King Mongkut Institute of Technology at Ladkrabang. The sample group used to develop the protection system model is a legal expert, 7 people, namely, graduate students of King Mongkut Institute of Technology Ladkrabang, 20 people. The tools used in this research are interview with legal experts and instructors, Knowledge measurement form, Online teaching and learning management system on privacy violation behavior in the use of social media Satisfaction questionnaire for learning styles and Assessment form for certification of integrated teaching and learning styles. The results from the test scores of the pre-school and post-test scores of the sample group showed that the post-test scores had an average score higher than before (before 10.80 and 13.71). In addition, it was found that the post-test scores had a standard deviation less than the test scores before learning (after learning is 1.29 and before 3.70), indicating that the post-test scores were higher than the previous test scores. Therefore, it can be concluded that the sample group when learning through the learning style resulted in higher average student scores.
Keywords: Sample (material); Blockchain Technology in Education and Learning